Using the ACTFL Guidelines in Evaluating Student-Teachers’ Speaking Proficiency - Hayfaa Kadhim Al Dihamat / Muna Mohammed Abbas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study aimed at Measuring English language speaking proficiency of Iraqi EFL student- teachers according to the ACTFL guidelines. Besides, assessing this proficiency of Iraqi EFL Student- Teachers at the Colleges of basic Education According to The ACTFL guidelines. The research used a descriptive analytical method. The researcher designs a test that sought to collect data relevant to process the study. The population of the study consists of the fourth-year students at the Departments of English, Colleges of Basic Education, for the academic year 2022-2023. These colleges are at University of Misan, University of Babylon, University of Diayla, Tikrit University, and university of Musol, the total number of the population is 1127. a sample of (63) student-teachers has been selected randomly from the English departments at the colleges of basic education at University of Babylon and University of Misan. The findings of this study show that Iraqi EFL student-teachers do not develop their linguistic proficiency through self-development and there is a clear weakness in the Iraqi EFL student-teachers’ linguistic proficiency.